ASSESSMENT MATERIAL SELECTION FOR CHAIN - SUBMERGED SCRAPPER CONVEYOR - Gunawan Gunawan; Amir Arifin; Irsyadi Yani; M. A. Ade Saputra; Barlin Oemar; Zulkarnain Ali Leman; Dendy Adanta; Akbar Teguh Prakoso (Asosiasi Peneliti Sriwijaya, 2023)
Chain–submerged scrapper conveyor bottom ash handling in the petrochemical industry has failed several times and was repaired with AISI 420, which can only operate for three months. AISI 420 is recommended in applications requiring moderate corrosion resistance, high hardness, excellent wear resistance, and good edge retention in cutting surfaces. The initial cracks and fractures occur in the pin-link joint hole, which causes chain failure. Some evaluation has been performed for both as-received and failed links. It can be concluded that chain link failure occurs due to fatigue failure with low-stress levels. Microstructure observation, XRD, and hardness properties showed no significant difference in both as-received and failed links. Since the operating conditions of the chain are in a corrosive environment, experiencing dynamic loading and working temperatures between 23 ºC and 60 ºC, the selection of HSL materials such as AISI 4140 should be considered.